Design of High-Bandwidth and High-Linearity Input Buffers for ADCs - Leonardo, David Barros (2021)
Nowadays on-chip Input Buffers (IBs) for direct conversion front-ends are realized with a higher voltage supply than that of the core voltage of the technology, mainly for linearity purposes. This, in turn, makes it mandatory to have more than one voltage source to supply a single chip in addition to having devices capable of handling higher voltages. This work explores the possibility of having IBs supplied with the technology’s core voltage to standardize all of the devices and reducing the different voltage supply sources and/or voltage regulators needed for operating the front-end drivers of the Analog to Digital Converters (ADCs). A new input buffer architecture will be presented and compared to some prior input buffer implementations in the same conditions. This new architecture presents good linearity and bandwidth results and can be used for input buffers with the added benefit of not needing higher voltages nor special devices. This new architecture is based off an existing one with another feedback loop to improved high-frequency peaking and linearity issues. This architecture achieves better results in bandwidth, a SNDR of 58 dB with and output voltage of 600 mV peak-to-peak differential. Furthermore, this buffer achieves a better efficiency linearity-wise when comparing to other buffers in the same conditions.